Challenges in the management of sickle cell disease during pregnancy in Senegal, West Africa. Issue 1 (2nd January 2018) - Faye, Blaise Felix; Kouame, Kouassi Berenger; Seck, Moussa; Diouf, Abdou Aziz; Gadji, Macoura; Dieng, Nata; Touré, Sokhna Aissatou; Sall, Abibatou; Toure, Awa Oumar; Diop, Saliou
ABSTRACT: Objectives: The aim of this study was to evaluate the maternal and fetal complications in pregnant patients with sickle cell disease (SCD) and find risk factors of stillbirth. Method: We conducted a prospective study in pregnant women with SCD. Demographic characteristics, maternal and fetal morbi-mortality, and outcome of pregnancies were described. Risk factors of fetal loss were evaluated by comparing the parameters of the pregnancies that led to a live birth with those interrupted. Results: We included 70 pregnancies in 58 women with SCD. The average age was 29.3 years. The average gestational age at the start of follow-up was 13 weeks. The occurrence of acute complications was significantly higher during pregnancy compared to the year before ( p < 0.05). Maternal mortality was 0%. Live birth rate was 80%. Fetal loss rate was 3.9 times higher in previous pregnancies that had not been monitored in hematology (71.8 versus 18.6%). Stillbirth was associated with nulliparity, high leukocytes or platelet counts ( p < 0.05). Conclusion: Pregnancy in SCD was associated with a high maternal morbidity and stillbirth. Nulliparity, high leucokocytes or platelet count were identified as risk factors of fetal loss.